Orographic Flow Influence on Precipitation During an Atmospheric River Event at Davis, Antarctica. Issue 2 (10th January 2022) - Gehring, Josué; Vignon, Étienne; Billault‐Roux, Anne‐Claire; Ferrone, Alfonso; Protat, Alain; Alexander, Simon P.; Berne, Alexis
Abstract: Intense snowfall sublimation was observed during a precipitation event over Davis in the Vestfold Hills, East Antarctica, from 08 to 10 January 2019. Radar observations and simulations from the Weather Research and Forecasting model revealed that orographic gravity waves (OGWs), generated by a north‐easterly flow impinging on the ice ridge upstream of Davis, were responsible for snowfall sublimation through a foehn effect. Despite the strong meridional moisture advection associated with an atmospheric river (AR) during this event, almost no precipitation reached the ground at Davis. We found that the direction of the synoptic flow with respect to the orography determined the intensity of OGWs over Davis, which in turn directly influenced the snowfall microphysics. We hypothesize that turbulence induced by the OGWs likely enhanced the aggregation process, as identified thanks to dual‐polarization and dual‐frequency radar observations. This study suggests that despite the intense AR, the precipitation distribution was determined by local processes tied to the orography. The mechanisms found in this case study could contribute to the extremely dry climate of the Vestfold Hills, one of the main Antarctic oases. Plain Language Summary: A case study of a snowfall event over Davis, Antarctica is presented. Despite the strong precipitation, snowfall did not reach the ground due to intense sublimation (transition from solid to gas state). Meteorological radar observations and atmospheric model simulations revealed that a dry downslope wind was responsible for the sublimation of snowfall below the cloud base. Despite the intense transport of moisture associated with the low pressure system during this event, almost no precipitation reached the ground at Davis. We found that the wind direction with respect to the main ridge upstream of Davis determined the intensity of the sublimation. This study suggests that despite favorable large‐scale conditions for intense snowfall at Davis, local processes related to the topography determined how much precipitation reached the ground. The mechanisms found in this case study could contribute to the extremely dry climate of the Vestfold Hills, one of the main ice‐free regions of Antarctica. Key Points: Despite intense moisture advection by an atmospheric river, foehn winds tied to orographic gravity waves (OGWs) led to snowfall sublimation The flow direction determined the intensity of the foehn and hence the temporal and spatial precipitation variability The event can be divided into three phases during which the features of the OGWs influenced the observed microphysics in distinct ways